STUDI TENTANG ISIM MUSYTAQ - Ali Asrun Lubis (IAIN Padangsidimpuan, 2014)
Isim Musytaq is “Isim is take from fi‟il”, it means that, noun originated from verb, like “read become reader”. In Arabic language obtain some words that contain from isim musytaq, like isim masdar, isim fa‟li, isim maf‟ul and soon. Isim Musytaq has i‟rab like the other isim that appropriate with the place and position where this word is put. It can be as isim marfu‟, isim mansub and isim that is majrur. In this case, Isim Musytaq can be Mudzakkar or Muannats, same with Mufrad, Mutsanna and Jamak.